ρ meson form factors and parton distribution functions in impact parameter space - Zhang 张, Jin-Li 金利 (Chinese physics C, 2025)
This study investigates the form factors and impact parameter space parton distribution functions of the ρ meson derived from the generalized parton distributions within the Nambu–Jona-Lasinio model framework, employing a proper time regularization scheme. We compare the charge , magnetic , and quadrupole form factors with lattice data. The dressed form factors, and , exhibit good agreement with lattice results; however, is found to be harder than what is observed in lattice calculations. The Rosenbluth cross section for elastic electron scattering on a spin-one particle can be expressed through the structure functions and . Additionally, the tensor polarization can also be formulated in terms of these form factors. We analyze the structure functions , and tensor polarization function ; our findings quantitatively align with predicted values across various limits. In impact parameter space, we examine parton distribution functions along with their dependence on longitudinal momentum fraction x and impact parameter . The width distributions in impact parameter space reveal that the range of the charge distribution is the most extensive. In contrast, the transverse magnetic radius falls within a moderate range, while the quadrupole distribution demonstrates the narrowest extent.